Modelling the Doha Round Outcome: A Critical view - Biswajit Dhar (Asia-Pacific Research and Training Network on Trade (ARTNeT), 2006)
In a series of papers published during the past few years, World Bank economists have provided detailed projections by simulating the possible outcomes of the Doha Round negotiations. The projections have been obtained by using the LINKAGE Model, which is considered to be a global dynamic computable general equilibrium (CGE) model. The latest version of the LINKAGE Model, viz. LINK6, which these papers have relied on, uses the Global Trade Analysis Program (GTAP). LINK6 incorporates 87 countries/regions and 57 sectors and uses a dataset that has been updated up to 2001. This latter feature of the model, according to the authors, has helped generation of far more realistic results than those that were using the earlier versions, which had incorporated data only up to 1997. This note attempts a critical assessment of the above-mentioned papers. At the outset, we would provide an analysis of the results that have been presented by looking at their implications for the developing countries in general and India, in particular. In the second part of the note, we would broadly allude to some of the methodological problems that are associated with the CGE models of the genre of the LINKAGE model. Our contention is that the limitations of these models, especially in terms of the assumptions on which they are based, deserve close scrutiny and that this dimension needs to be kept in view as the results obtained from studies are read.
Keywords: F1; 330; Doha Round Negotiations; WTO